An evaluation of Nova Scotia's alcohol ignition interlock program. (March 2017) - Vanlaar, Ward G.M.; Mainegra Hing, Marisela; Robertson, Robyn D.
Highlights: Nova Scotia's alcohol ignition interlock program was evaluated. Methods used include survival, time series and logistic regression analysis. Data show a reduction in recidivism of up to 90%. There was a significant decrease in alcohol-related serious and fatal crashes. Program violations decreased over time suggesting learning behavior. Abstract: Alcohol ignition interlock programs for offenders aim to reduce recidivism among convicted drink drivers. This study presents an evaluation of Nova Scotia's interlock program implemented in 2008 in order to assess its effectiveness to reduce impaired driving and to help identify areas for improvement. Data used include conviction and crash records of individual participants; provincial monthly counts of alcohol-related charges, convictions and fatal and serious crashes; and interlock logged events. Methods used include descriptive statistics, survival analysis, time series and logistic regression analysis. With respect to specific deterrence (i.e., preventing recidivism) there was a 90% reduction in recidivism among voluntary participants since participation in the interlock program and a 79% reduction after these participants exited from the program. With respect to general deterrence (i.e., referring to a preventative effect on the entire population of drivers in Nova Scotia) there were temporary decreases in the numbers of alcohol-related charges (13.32%) and convictions (9.93%) and a small significant decrease in the number of fatal and serious injury alcohol-related crashes, following the implementation of the program. The evidence suggests the interlock program was better at preventing harm due to alcohol-impaired driving than the alternative of not using the interlock program. Recommendations were formulated supporting the continuation of the interlock program in Nova Scotia.